ANALISIS DAMPAK PERKEMBANGAN PARIWISATA TERHADAP PERUBAHAN KONDISI SOSIAL EKONOMI MASYARAKAT DESA KERSIK TUO KECAMATAN KAYU ARO KABUPATEN KERINCI - Dwi Pratiwi Wulandari (Ensiklopedia of Journal, 2019)
Tourism is an important sector developed by the government in the hope that it can have a positive impact on changing socio-economic conditions in a better direction. The development of Mount Kerinci natural tourism over the past six years is expected to have a positive impact on changes in the socio-economic conditions of the Kersik Tuo Village community as a center for mobility and transit for tourists, namely changes in business opportunities and employment opportunities for the community. Based on the results of the study, currently the development of tourism has succeeded in increasing business opportunities which previously had 7 business opportunities to become 14 business opportunities, and employment opportunities which initially only had 4 types of employment opportunities then increased to 10 types of employment opportunities. With increasing business opportunities and employment opportunities means that the development of tourism has had a positive impact on changes in the socio-economic conditions of the Grit Tuo Village community.